How are mental simulations updated across sentences? - Hoeben Mannaert, Lara N.; Dijkstra, Katinka; Zwaan, Rolf A. (Memory & Cognition, 2019)
We examined how grounded mental simulations are updated when there is an implied change of shape, over the course of two (Experiment 1) and four (Experiment 2) sentences. In each preregistered experiment, 84 psychology students completed a sentence–picture verification task in which they judged as quickly and accurately as possible whether the pictured object was mentioned in the previous sentence. Participants had significantly higher accuracy scores and significantly shorter response times when pictures matched the shape implied by the previous sentence than when pictures mismatched the implied shape. These findings suggest that during language comprehension, mental simulations can be actively updated to reflect new incoming information.